6x+9=9x-6

Simple and best practice solution for 6x+9=9x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+9=9x-6 equation:


Simplifying
6x + 9 = 9x + -6

Reorder the terms:
9 + 6x = 9x + -6

Reorder the terms:
9 + 6x = -6 + 9x

Solving
9 + 6x = -6 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
9 + 6x + -9x = -6 + 9x + -9x

Combine like terms: 6x + -9x = -3x
9 + -3x = -6 + 9x + -9x

Combine like terms: 9x + -9x = 0
9 + -3x = -6 + 0
9 + -3x = -6

Add '-9' to each side of the equation.
9 + -9 + -3x = -6 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = -6 + -9
-3x = -6 + -9

Combine like terms: -6 + -9 = -15
-3x = -15

Divide each side by '-3'.
x = 5

Simplifying
x = 5

See similar equations:

| 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 | | x=4(x-1)+1 | | y=2cos(x^2) | | 6x+28=2x+52 | | x^2+6x+8=o | | 5s+s^2+4=0 | | lnx-ln(x+4)=2 | | 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 | | (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 |

Equations solver categories